P206 Acute hypercapnic respiratory failure: application of a novel human factors approach to improve recognition and management. (December 2018) - Draicchio, D; Pick, H; Smith, S; Taylor, N; Mullaney, E; Lowrey, G
Abstract : Background: Acute Hypercapnic Respiratory Failure (AHRF) is a medical emergency. Data from the National COPD Audit Programme identified that only 42.7% of patients requiring ventilatory support received it in less than 3 hours and 45% of patients admitted nationally had no oxygen prescription. This falls short of the quality standards set by NICE for COPD in adults. We aimed to improve the recognition and management of AHRF in hospital inpatients using interventions developed from a novel Human Factors approach. Methods: Cases of AHRF were reviewed as safety critical incidents using a Human Factors approach and from this a Bow-Tie model created. This helped identify barriers which facilitate effective management and threats to these which compromise patient care. Multi-disciplinary workshops were undertaken to discuss how safety critical barriers could be strengthened and from this a set of interventions derived. Data was collected before and after the intervention by retrospective case note review of patients with AHRF (pH <7.35, pCO2 >6.5) on blood gas analysis. Results: 48 case notes were reviewed pre-intervention and 50 reviewed post-intervention. There was a significant increase in the recognition of AHRF in the post-intervention group (p=0.042) and a significant increase in the patients who were prescribed oxygen; 86% post-intervention versus 55.3% pre-intervention (p<0.001). In addition, there was a significant increase in an escalation decision in the post-intervention group (p=0.006). 82% of patients had a documented ceiling of care decision versus 56.3% in the pre-intervention group. There was a significant improvement in 30 day mortality (p=0.016) in the post-intervention group but not in inpatient mortality. 55.6% of patients in the post-intervention group had an ABG done within 1 hour of starting non-invasive ventilation (NIV), compared to 26.3% in the pre-intervention group, but the mean time from admission to NIV was not statistically different pre- and post-intervention (195.4 min vs 220 min). This may be due to the small number starting NIV failing to show a significant difference. Conclusions: The interventions developed using a Human Factors based method resulted in improvement in the recognition and management of AHRF and subsequent outcomes. Human factors methods and Bow-Tie analysis could be used in other medical scenarios to improve outcomes.